2020
DOI: 10.1075/intp.00045.nou
|View full text |Cite
|
Sign up to set email alerts
|

An interpreter advantage in executive functions?

Abstract: Abstract The aim of this systematic literature review was to answer the question of which executive function is most affected by interpreter training and experience. We used the ‘unity and diversity’ framework of executive functions to distinguish between three executive components: Response and Distractor Inhibition, Shifting, and Updating. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
3
9
0
1
Order By: Relevance
“…In cross-sectional between-group comparisons, 69% of publications on shifting supported an interpreter advantage, while all longitudinal studies (100%) presented positive evidence. The results aligned with the conclusion in Nour et al (2020). Besides, the interpreter advantage in shifting was also shown in the meta-analysis of two shifting tasks (SMD = 0.68 for WCST and SMD = -0.32 for Task-switching).…”
Section: Shiftingsupporting
confidence: 86%
See 4 more Smart Citations
“…In cross-sectional between-group comparisons, 69% of publications on shifting supported an interpreter advantage, while all longitudinal studies (100%) presented positive evidence. The results aligned with the conclusion in Nour et al (2020). Besides, the interpreter advantage in shifting was also shown in the meta-analysis of two shifting tasks (SMD = 0.68 for WCST and SMD = -0.32 for Task-switching).…”
Section: Shiftingsupporting
confidence: 86%
“…(Diamond, 2013;Gilbert and Burgess, 2008;Miyake et al, 2000). Nour et al (2020) found evidence for the interpreter advantage in shifting and updating, but not in inhibition. In the mean times, the meta-analysis by Wen andDong (2019, cut-off before Oct.30, 2018) and Mellinger andHanson (2019, cut-off before Dec. 2016) revealed significant effects for the interpreter advantage in STM and WM.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations